Induction of seed coat water impermeability during maturatiof erythrina speciosa seeds - Molizane, Debora Manzano [UNESP]; Carmello-Guerreiro, Sandra Maria; Barbedo, Claudio José (FapUNIFESP (SciELO), 2020)
Dormancy is a physiological process that allows seeds to survive in unfavorable environments by preventing their germination. For a large number of species, seed desiccation at the end of maturation is common, and for some of these seeds, this includes seed coat water impermeability (SCWI). The environmental conditions in which the mother plant develops affect the seed maturation process, causing variations in both seed physiological quality and the onset of physical dormancy. In this study, we analyzed the induction of SCWI in immature seeds of Erythrina speciosa by artificial drying. Seeds at three stages of immaturity were dried gradually for subsequent evaluation of their germination. At each level of drying, the anatomical structure of the seed coat was also analyzed. Artificial drying was able to induce SCWI in immature seeds. Furthermore, environmental conditions affected at which stage of maturity SCWI began, and they affected development of desiccation tolerance. However, unlike other species, there were no anatomical differences related to this SCWI (whether by natural drying or artificial drying) and, therefore, in E. speciosa seeds, SCWI may be related to biochemical differences in the seed coat.
Indução da impermeabilidade do tegumento em relação a água durante a maturação em sementes de erythrina speciosa
Keywords: Desiccation tolerance; Dormancy; Drying; Tropical tree species